Prince George's Parish, Montgomery County, Md., record book - Prince George's Parish (Montgomery County, Md.)
Record book (169 pages) containing minutes of vestry meetings and register. Rectors mentioned in the minutes include Thomas Allen, George Murdock, Thomas G. Read, and Alexander Williamson.
Negative photostat produced from original.
Episcopal church.
Collection material in English.
Keywords: Allen, Thomas; Murdock, George; Read, Thomas G; Williamson, Alexander; Episcopal Church -- Maryland; Registers of births, etc. -- Maryland -- Montgomery County; Maryland -- Church history; Montgomery County (Md.) -- Church history; Montgomery County (Md.) -- Genealogy; Clergy